Effects of microwave electric field on the structure and association behaviour of asphaltenes: MD and DFT study. (16th January 2023) - Fan, Xiayu; Shang, Hui; Li, Jun; Zhang, Wenhui; Duan, Aijun
Graphical abstract: Highlights: ESP of asphaltene molecules can predict the MD behavior accurately. Microwave field changes T -shape to π-π stacking, reducing H-bond interaction. The stacking types of asphaltene molecules highly determines their aggregation. Suitable microwave significantly inhibits the aggregation of asphaltene molecules. An optimum microwave power is desirable for viscosity reduction. Abstract: Asphaltenes are prone to aggregation through complex macromolecular interactions, resulting in high-viscosity crude oil. The aggregation behaviour of asphaltene in different solvents under microwave fields was simulated and studied by molecular dynamics in this research. Furthermore, the nature of asphaltene monomers and the interactions of dimers were investigated by density functional theory to explore the contribution of the microwave electric field on asphaltene aggregation. The results show that the microwave electric field is beneficial for breaking T -shaped stacking and forming π-π stacking, which greatly reduces hydrogen bonds and weakens the molecular interactions, thus effectively inhibiting the proceeding of aggregation. Applying an electric field with a strength of 8 V/nm has been found to have the best asphaltene dispersion efficiency. This work innovatively reveals the microscopic behaviour of asphaltenes in various solvents by microwave irradiation, contributing to the disassociation of heavy oil micelles with microwave introduction.